Is Insulin Resistance a High-Risk Factor for Postmenopausal Endometrial Cancer: Insights from the Triglyceride Glucose (TyG) Index and the Metabolic Score for Insulin Resistance (METS-IR) - Gao S; Wang J; Wang T; Wang J (International Journal of Women's Health)
Songkun Gao,1 Jinhua Wang,2 Tong Wang,1 Jiandong Wang1 1Gynecologic Oncology Department,Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing Maternal and Child Health Care Hospital, Beijing, People’s Republic of China; 2Department of Obstetrics and Gynecology, Beijing Youan Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Tong Wang; Jiandong Wang, Gynecologic Oncology Department, Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing Maternal and Child Health Care Hospital, Qihelou Street, Dongcheng District, Beijing, 100006, People’s Republic of China, Email fcyywt@ccmu.edu.cn; wangjiandongxy@ccmu.edu.cnPurpose: To evaluate the insulin resistance in patients with menopause who were newly diagnosed with endometrial cancer and its association with disease development.Methods: The study included 356 patients with menopause who underwent hysteroscopy at Beijing Obstetrics and Gynecology Hospital between September 2013 and July 2018. Data on age, height, weight, menarche and menopausal age, pregnancies, births, and family history of tumors, hypertension, and diabetes were collected. Blood tests provided fasting blood glucose, triglycerides, total cholesterol, high-density lipoprotein, and low-density lipoprotein levels. Pathological testing determined whether patients had endometrial cancer or precancerous lesions. Differences in influencing factors between patients with endometrial cancer or precancerous lesions and those with normal or benign conditions were analyzed using univariate analysis. Quartile grouping of the Metabolic Score for Insulin Resistance (METS-IR) and Triglyceride-Glucose (TyG) index were applied to examine the impact of different insulin resistance on the development of endometrial cancer or precancerous lesions.Results: Univariate analysis revealed that the proportion of patients with hypertension and diabetes was significantly higher among those with endometrial cancer and precancerous lesions. METS-IR and TyG levels were significantly increased in patients with endometrial cancer and precancerous lesions. The quartile grouping results of METS-IR and TyG suggested that age, BMI, FBG, TG, hypertension, and diabetes prevalence rates increased with an increase in METS-IR or TyG, whereas lipid indicators were negatively correlated and unstable Logistic regression suggested that none of the above influencing factors and METS-IR or TyG were related to the pathological results of the patients.Conclusion: Patients with endometrial or precancerous lesions showed evidence of insulin resistance compared to others, though this was not directly associated with disease presence. This study provides relevant information for preventing of endometrial cancer in the future. Larger studies are needed to evaluate the role of METS-IR and TyG in endometrial cancer prevention.Keywords: postmenopausal, endometrial cancer, insulin resistance, METS-IR, TyG